1977
DOI: 10.2134/agronj1977.00021962006900060024x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus and Potassium on Soybean Nodules and Seed Yield1

Abstract: Much of the nutritional research on soybean [Glycine max (L.) Merrill] nodulation has been under greenhouse or laboratory conditions. Additional field data are needed on the influence of nutrients on nodulation and other plant characteristics. The purpose of this investigation was to determine under field conditions the effects of P and K fertilization on number and weight of soybean nodules; the chemical composition of leaves, nodules, and seed; the number of pods per plant; and seed yield. Annual P rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 6 publications
5
32
0
3
Order By: Relevance
“…Fresh and dry weights of nodules were varied significantly (p<0.05) among the treatments, T 5 showed significantly high fresh and dry weights. This was confirmed by the study of Jones et al (1977) who stated that the number and weight of soyabean nodules increased as K nutrition improves. …”
Section: Nodule Formationmentioning
confidence: 62%
“…Fresh and dry weights of nodules were varied significantly (p<0.05) among the treatments, T 5 showed significantly high fresh and dry weights. This was confirmed by the study of Jones et al (1977) who stated that the number and weight of soyabean nodules increased as K nutrition improves. …”
Section: Nodule Formationmentioning
confidence: 62%
“…Esses resultados demonstram a importância da disponibilidade no solo dos nutrientes P e K, citada por Werner (1984) e Jones et al (1977), para que possa haver boa nodulação nas plantas leguminosas e conseqüente fixação de nitrogênio.…”
Section: Resultsunclassified
“…Stammel (1968) constatou que a aplicação de fósforo proporcionou aumento altamente significativo na produção de matéria seca do trevo-vermelho (Trifolium pratense L.). Segundo Jones et al (1977), a adubação fosfatada também influenciou a nodulação da soja (Glycine max (L.) Merr.) e fez com que aumentasse o número de nódulos por planta e o tamanho dos nódulos.…”
Section: Introductionunclassified
“…Therefore, the responses of dry matter production and yield components to P fertilizer were less marked in the field experiments than in the pot experiments. Jones et al (1977) reported that nodulation and the pod formation response of soybeans fertilized with both P and potassium were greater than the responses to either nutrient applied alone. Furthermore, there were varietal differences in the response of seed yield to the amounts of P and potassium applied in soybeans (Matsunaga and Matsumoto, 1984).…”
Section: Discussionmentioning
confidence: 99%